ANALISIS PENDAPATAN USAHA GULA AREN DI DESA TANJUNG SELOKA UTARA KECAMATAN PULAU LAUT SELATAN KABUPATEN KOTABARU - Rika sylvia; Ni Nyoman Suarniki (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, The purpose of this study was to analyze the business income of palm sugar in Tanjung Seloka Utara Village, Pulau Laut Selatan Subdistrict, Kotabaru Regency. The type of research used is quantitative descriptive, with sampling using purposive sampling. The results of this study indicate that the palm sugar business has a R / C value of more than 1, this indicates that every Rp. 1, - the costs incurred by each business owner were able to give a refund in the form of revenue of Rp.9.8, - for Mr. H. Samad, while Mr. Suburi amounted to Rp. 62.96, - and Mrs. Suharni for Rp. 1.84, - as for Mrs. Santi Rp. 24.75, -. This means that the total revenue is still greater than the total production costs, and the palm sugar business activities are still experiencing profits.